The Transmission of Monetary Policy Trough Bank Lending Channel In Indonesia - Saraswati, Ajeng Ayu; Mubin, M. Khoerul (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of policy interest rates (BI rate), GDP, and bank characteristics (size, liquidity, equity, profitability) on the volume of credit through bank lending channels in Indonesia. The study utilize data of 26 state commercial bank in Indonesia. Bank characteristic variables are measured by various approaches related to bank balance sheets. Data collection is retrieved from the websites of Bank Indonesia, the Financial Authority Services, and Indonesian Central Statistics Agency. This study examines the volume of credit distributed by Indonesian commercial bank during 2006 to 2016. Utilizing the GMM method, we found that the policy interest rate (BI rate), GDP, and bank characteristics (size, liquidity, equity, and profitability) significantly affect the volume of credit through bank lending channel in Indonesia.